The Influence Of Enterprise Risk Management (ERM) On Profitability, Cost Of Debt, And Company Value: The Role Of Moderation Of Environmental, Social, Governance (ESG) In Asean-5 Countries Period 2017-2021 - Ervina Kwintana; Dewi Hanggraeni (International Journal of Economics Development Research (IJEDR), 2023)
This study aims to determine the effect of Enterprise Risk Management (ERM) moderated by Environmental Social Governance (ESG) performance on profitability, cost of debt and firm value. This study sampled 148 companies in ASEAN-5 countries during the 2017-2021, with 740 observations. The hypothesis was tested using the Ordinary Least Square method and showed. It showed moderation increases the significance of ERM implementation on profitability, cost of debt and firm value. The study’s results also found that the environmental and social pillars had a significant positive effect. In contrast, the governance pillar did not significantly affect profitability, debt costs and firm value. The findings in this study suggest that regulators make more comprehensive rules regarding the implementation of ERM and ESG.